SELEBRITI ENDOSER DAN CITRA MEREK PADA KEPUTUSAN PEMBELIAN KOSMETIK PADA TOKO MS.GLOW MARAPALAM - Maria Magdalena; Jeki Algusri; Lusti Ika Nirmala Sari (Jurnal Bina Bangsa Ekonomika, 2024)
In today's technological growth, beauty products have become a primary need, especially for women, who are the main targets of the beauty industry. The purpose of this study was to determine the influence of endoser celebrity variables and brand image on cosmetic purchasing decisions at Ms. Glow Marapalam store. Through the questionnaire method with samples using the slovin formula, there were 85 respondents. Meanwhile, the population in this study is consumers who buy skintific products in January-June 2023 at Ms Glow Marapalam Store. On hypothesis testing through the t test (Partial Test) shows the Celebrity Endoser and Brand Image studied proved to significantly influence the Purchase Decision. The results of this study show that endoser celebrities and brand image have a positive and significant influence on cosmetic purchasing Ms Glow in stores Marapalam